Crypto Assets and Regulation: Taxonomy and Framework Regulatory of Crypto Assets in Indonesia - Afif Noor; Moh. Arifin; Deni Parama Widia Astuti (Universitas of Muhammadiyah Makassar, 2023)
Cryptocurrency is a new investment commodity that is growing fast in Indonesia. Crypto assets have different taxonomies from one another. For this reason, this research aims to identify the taxonomy of crypto assets as digital assets and analyze the framework of regulation for crypto assets as an investment commodity in Indonesia using normative juridical methods. This research uses statute and an analytical approach. The research data is taken from secondary data sources. The results study show that to create proper regulation of crypto assets in Indonesia is crucial to classify the types of crypto assets appropriately. Although the Indonesian government has issued several specific rules related to crypto assets, such as Bappebti Regulation No. 8 of 2021, these regulations have not provided sufficient legal certainty and protection for crypto asset users who have a broad dimension and scope as digital assets that can be used as a means of payment and investment and involve cross-sectoral. Therefore, stronger regulations in the form of laws are needed to provide legal protection for cryptooassettusers in Indonesia.